2j+9=-j

Simple and best practice solution for 2j+9=-j equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2j+9=-j equation:



2j+9=-j
We move all terms to the left:
2j+9-(-j)=0
We add all the numbers together, and all the variables
2j-(-1j)+9=0
We get rid of parentheses
2j+1j+9=0
We add all the numbers together, and all the variables
3j+9=0
We move all terms containing j to the left, all other terms to the right
3j=-9
j=-9/3
j=-3

You can always share this solution

See similar equations:

| X(3.44)+x(4.33)=49.29 | | 9-4t=-3t | | x-7.5=16.4 | | m?5=180°-81°=99° | | -1.3x+7=31 | | 0.04x=0.01 | | (2x-7)(6x+7)=0 | | 3x-2/3x=3/14 | | 48p=12 | | 0=-4.9t^2+9.8t | | -11-x=-17 | | 48÷p=12 | | 14x-1=-57 | | 9*x+1/7=18 | | 5x-2=-4x+12 | | 14x–61=2x+35 | | 2x+35=14x–61 | | 134=5x+84 | | 5(x-5)-x=4x | | 67=5x+84 | | x+34=11x-56 | | x-26=x+37 | | 9p?2=?10p-2 | | 8b-7=17 | | 5x+16=7×-14 | | 3y=5-6 | | 6r-5=8r-23 | | 4+15x=-1 | | -2-8x-9=-9x-10 | | 5–10=5(x–2) | | 5x=7=73 | | -3-4y=20 |

Equations solver categories